Elastic stability of plate simply supported on four sides subjected to combined bending shear and patch loading. (October 2016) - Tong, Genshu; Feng, Yixiao; Tao, Wendeng; Zhang, Lei
Abstract: In the paper the buckling of simply supported plates under combined bending, shear and patch loading is studied in this paper with ANSYS, such a stress state occurs in girder supporting over-head crane. The effect of the width-to-height ratio of the plate and the width of patch loading on the interactive curves are analyzed in detail. And, it is found that the effect of the width of patch loading on the nondimensional interaction curves of bending and patch loading and the interactive curves of shear and patch loading is small. Through detailed FEM analysis, the interaction curves between any two among three stress components are obtained, and then through a designed numerical strategy the nondimensional 3D interactive surfaces of bending, shear and patching loading is found. An approximate equation for the 3D surface is proposed, comparison with the FE results shows that the proposed formula has excellent accuracy. Highlights: The buckling of simply supported plates under combined bending shear and patch loading is studied. The effect of the width of patch loading on the nondimensional interaction curves is small. An approximate equation for the interactive surface of bending shear and patching loading is proposed.